2023
DOI: 10.3390/ijerph20032421
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Biomarker Profile of Pre-Frail and Frail People: A Cross-Sectional Analysis from UK Biobank

Abstract: Objective: This study aimed to compare the biomarker profile of pre-frail and frail adults in the UK Biobank cohort by sex. Methods: In total, 202,537 participants (67.8% women, aged 37 to 73 years) were included in this cross-sectional analysis. Further, 31 biomarkers were investigated in this study. Frailty was defined using a modified version of the Frailty Phenotype. Multiple linear regression analyses were performed to explore the biomarker profile of pre-frail and frail individuals categorized by sex. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…Considering all these biomarkers collectively, the ML approach shows promise in enhancing the capability to detect frailty with improved sensitivity and specificity, especially since frailty involves multiple biological systems. The feature importance of the BA and frailty predictors revealed that cystatin C, glycated hemoglobin, creatinine, hemoglobin and Creative protein are among the most important features, which is consistent with many previous findings [6,8,9,18,28,61].…”
Section: Advantages Of Machine Learning and Ba And Frailty Status Pre...supporting
confidence: 91%
“…Considering all these biomarkers collectively, the ML approach shows promise in enhancing the capability to detect frailty with improved sensitivity and specificity, especially since frailty involves multiple biological systems. The feature importance of the BA and frailty predictors revealed that cystatin C, glycated hemoglobin, creatinine, hemoglobin and Creative protein are among the most important features, which is consistent with many previous findings [6,8,9,18,28,61].…”
Section: Advantages Of Machine Learning and Ba And Frailty Status Pre...supporting
confidence: 91%
“…Using this frailty index, our results are consistent with prior literature using other frailty indices. In large, cross‐sectional studies, low testosterone has proven to be an independent predictor of frailty 17 . This finding has been replicated in populations of patients with chronic liver disease, cardiovascular disease, and end‐stage renal failure.…”
Section: Discussionmentioning
confidence: 80%
“…low testosterone has proven to be an independent predictor of frailty. 17 This finding has been replicated in populations of patients with chronic liver disease, cardiovascular disease, and end-stage renal failure. However, limited data exists regarding the relationship of low testosterone and frailty among surgical patients.…”
Section: Discussionmentioning
confidence: 81%
“…A recent intervention experiment in mice also found that supplementation with a mixture of Opuntia ficus-indica, Theobroma cacao, and Acheta domesticus increased the abundance of Eubacterium coprostanoligenes in obese mice, thereby reducing serum cholesterol levels 49 . Meanwhile, a large-scale study based on the UK Biobank found that lower levels of total, low-density lipoprotein (LDL), and high-density lipoprotein (HDL) cholesterol were associated with a higher prevalence of frailty 50 . It can be deduced from this that the higher the abundance of Eubacterium coprostanoligenes , the lower cholesterol level may be, which may increase the risk of frailty.…”
Section: Discussionmentioning
confidence: 99%